Modern management of T1 rectal cancer by transanal endoscopic microsurgery: a 10‐year single‐centre experience. (2nd July 2018) - Jones, H. J. S.; Hompes, R.; Mortensen, N.; Cunningham, C.
Abstract: Aim: Minimally invasive, organ‐sparing surgery has been used increasingly for early rectal cancer in recent years. However, local recurrence remains a concern. This study presents a 10‐year single‐centre experience of recurrence after local excision for T1 rectal cancer. Method: Data were collected prospectively on all patients undergoing local excision by transanal endoscopic microsurgery (TEM) in a single institution. Data covering a 10‐year period were analysed. Results: In all, 192 patients underwent TEM for rectal cancer; 70 of these had T1 tumour in the TEM specimen and did not have preoperative radiotherapy. Four were managed with completion surgery following TEM and a further six had radiotherapy; 60 underwent surveillance alone. Local recurrence occurred in six patients; three underwent salvage surgery. Estimated local recurrence at 3 years was 7.2% for the surveillance alone group. Conclusions: Local recurrence rates were lower than previous studies. Better preoperative assessment, more effective local excision surgery and postoperative radiotherapy may be contributory factors to a better‐than‐predicted outcome. Local excision should be offered as part of standard of care for T1 rectal cancer in the presence of good preoperative selection and meticulous surveillance.